2022
DOI: 10.3390/ma15207324
|View full text |Cite
|
Sign up to set email alerts
|

Wear Properties of Conventional and High-Translucent Zirconia-Based Materials

Abstract: This study investigated the two-body wear resistance of a first generation 3 mol% yttria-stabilized tetragonal zirconia polycrystal (3Y-TZP), a second generation 3Y-TZP, a third generation 4 mol% yttria partially stabilized zirconia (4Y-PSZ), a 5 mol% yttria partially stabilized zirconia (5Y-PSZ), and a type III gold alloy (Aurocast 8), performed using opposing antagonistic cusps made out of the same material. Eight cylindrical specimens were prepared for each material (n = 8) for a total of forty specimens (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…The author reported that the polished zirconia produced less abrasion than glazed zirconia or polished feldspathic ceramic. Recently, De Angelis et al [64] reported a wear resistance for the ultra-translucent zirconia closest to that of type III gold alloy. On the other hand, Albashaireh et al [65] showed how the degree of wear of the antagonist tooth enamel was significantly less in zirconia restorations compared to feldspar porcelain restorations.…”
Section: Discussionmentioning
confidence: 99%
“…The author reported that the polished zirconia produced less abrasion than glazed zirconia or polished feldspathic ceramic. Recently, De Angelis et al [64] reported a wear resistance for the ultra-translucent zirconia closest to that of type III gold alloy. On the other hand, Albashaireh et al [65] showed how the degree of wear of the antagonist tooth enamel was significantly less in zirconia restorations compared to feldspar porcelain restorations.…”
Section: Discussionmentioning
confidence: 99%
“…Dental implants used to restore missing teeth do not have periodontal ligament nor mechanoreceptors and are not able to move in the bone, which means that the natural mechanisms of adapting to occlusion do not function in their case [ 23 ]. Crowns on implants made of ceramic materials or zirconium oxide are additionally characterized by greater hardness and a lower modulus of elasticity [ 24 ] as well as lower ability to wear than natural human enamel [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several papers investigated the in vitro wear resistance of restorative materials opposing either human enamel antagonists or dedicated artificial abraders [ 25 , 46 ], underlining the effect of different antagonist materials on the wear rate of tested specimens. Furthermore, few studies analyzed the wear behavior of dental materials opposing themselves, which seems particularly interesting for simulating the clinical scenario of restored occlusal surfaces occluding in a full-mouth rehabilitation [ 26 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dental zirconia is available in various compositions (3–5 mol% yttria‐stabilized) which affect its mechanical and physical properties 10 . A cusp‐on‐cylinder 2‐axis wear study of various ceramics opposing themselves reported that 5 mol% yttria‐stabilized (5Y) zirconia experienced more wear than 4Y or 3Y zirconia 11 …”
Section: Introductionmentioning
confidence: 99%
“…10 A cusp-on-cylinder 2-axis wear study of various ceramics opposing themselves reported that 5 mol% yttria-stabilized (5Y) zirconia experienced more wear than 4Y or 3Y zirconia. 11 Therefore, the main objective of this study was to measure and compare the wear of lithium disilicate opposed by various restorative materials (3Y zirconia, 5Y zirconia, lithium disilicate, and feldspathic porcelain) and enamel. Microhardness and scanning electron microscopy were performed to help understand the mechanisms of wear.…”
mentioning
confidence: 99%